The effect of the pseudostem extract of ambon banana on the number of lymphocytes and fibroblasts in gingivitis : an experimental study - andriani, Ika; Medawati, Ana; Lestra, Citra; Salsabila, Millati; Khairunnisa, Putri Nabilla (Padjadjaran Journal of Dentistry, 2023)
ABSTRACTIntroduction: Gingivitis is an inflammation of the soft tissue that supports the teeth. Chemical treatment in the form of mouthwash, such as chlorhexidine, is often recommended. However, long-term use of chlorhexidine mouthwash will cause side effects, such as allergies, irritation of the oral cavity, and discoloration of the oral mucosa and teeth. Therefore, natural alternative materials containing flavonoids, saponins, and tannins that can cure gingivitis are needed. These ingredients are found in the pseudo stem of the Ambon banana. This research aims to analyze the effect of applying the pseudostem extract of Ambon banana on the number of lymphocytes and fibroblasts in treating gingivitis. Methods: This study was an in vivo laboratory experimental study with a post-test control group. The study used 45 Sprague Dawley rats which were divided into 3 groups, namely the positive control group (chlorhexidine gel), negative control (gel base), and treatment (Ambon Banana pseudostem extract gel). The gingiva on the mandibular incisor of the rat was ligated, then the gel was applied to the gingiva. Decapitation of rats was carried out on days 1, 3, 5, 7, and 9, and then made histological preparations with HE. Staining and observations were later made. Data analyzed using Kruskal-Wallis test. Results: The results showed that Ambon banana false stem extract gel reduced the number of lymphocyte cells with a significant difference of p=0.016 (p<0.05) and increased fibroblasts at p=0.85 (p>0.05). Conclusion: The pseudostem extract gel of Ambon banana reduced the number of lymphocyte cells and increased fibroblasts in gingivitis treatment.Keywords: fibroblasts, gingivitis, lymphocytes, pseudostem of ambon banana